Critical Role of Mission Valence as Moderator in Leadership and Public Service Motivation - Dina Lesmana (Budapest International Research and Critics University, 2022)
The organization's mission is mostly written and recorded as documents weighted to understand and serve as suggestions for good orientation for individuals to direct themselves as employees. This research aims to analyze the role of Mission Valence as a variable that moderates the influence of public service leadership on public service motivation in West Java. Explanatory survey deduction research on sub-district employees in West Java Province. The number of samples is 327 randomly selected. Inferential data analysis using SEM procedure covariance the study results show that Vision strengthens the relationship between leadership and performance but not for employee motivation. Leadership that can ensure a balance of administrative and local orientation, decision making, decision making, focus on, and control can encourage PSM Mission to moderate the influence of leadership on PSM. The practical implication is the importance of developing a mission to strengthen leadership that can encourage motivation in regional government institutions.